RETRACTED: Rehman et al. Piperine Regulates Nrf-2/Keap-1 Signalling and Exhibits Anticancer Effect in Experimental Colon Carcinogenesis in Wistar Rats. Biology 2020, 9, 302 - Muneeb U. Rehman; Summya Rashid; Azher Arafah; Wajhul Qamar; Rana M. Alsaffar; Ajaz Ahmad; Nada M. Almatroudi; Saeed M. A. Alqahtani; Shahzada Mudasir Rashid; Sheikh Bilal Ahmad (Biology)
The journal retracts the article, “Piperine Regulates Nrf-2/Keap-1 Signalling and Exhibits Anticancer Effect in Experimental Colon Carcinogenesis in Wistar Rats” [...]